(1-x) Li1-yNayM1-zTizO2 x LiM2-zTizO4 Layered-Spinel nanoparticles as Promising dual positive electrode for Lithium-Ion Batteries and Sodium-Ion Batteries (2022)
ABSTRACT: The demand for high-capacity batteries is increasing rapidly with the upcoming energetic needs of an ever increasing population, especially in the transportation sector. Lithium-ion battery (LIB) has emerged as an attractive technology, however the main restriction is his low energy density1. To make a post-transition possible the sodium-ion battery (SIB) are among the most promising alternatives due sodium is abundant, there are enormous availability and It's low cost2. Besides, the electrochemical principles governing LIB and SIB batteries are quite similar3. Nevertheless, for both emerging alternatives it is necessary to find more suitable electrode materials. Therefore, nowadays, different electrode materials have been explored to increase the capacity of those batteries. Specially, the layered-spinel structure has been used to improve the initial specific capacity and stability electrode materials. The Na-layered structure cathode facilitates Li+-ion diffusion in the structure4. Besides the incorporation of Ti4+ in the LiMn2O4 spinel phase is performed with the purpose of improving its stability by averting the Jahn-Teller effect of the Mn3+ and decreasing Mn2+ dissolution towards the electrolyte during cycling since Ti-O provides a higher binding energy (662 kJ/mol) than for Mn-O (402 kJ/mol)1. The aim of this investigation is to estimate the optimal stoichiometry in the (1-x)Li1-yNayM1-zTizO2x LiM2-zTizO4 layered-spinel by varying the concentration of Na+ and to assess the effects of the Na+ addition in the cycling stability of the active material. A facile sol-gel method is presented to develop new composite materials for LIB and SIB. Analysis of XRD patterns confirmed the existence of a spinel layered composite where the peaks can be indexed to the cubic spinel structure (Fd3̅m) and layered structure (c2/c) for the (020) superlattice peak at 20.5°5. For LIB cycling was performed typically between 4.8 and 2.0V vs. Li|Li+ at a constant current of 29.0 mAg-1, equivalent to 0.1 C-rate. The stoichiometry 0,5Li0.9Na0.1Mn0.4Ni0.5Ti0.1O2-0,5LiMn1.4Ni0.5Ti0.1O4 showed an initial specific capacity, ca. 141 mAhg-1 but later it presented increasing of the specific capacity, ca. 180 mAh g-1 at 15st cycling exhibiting 98% of its charge capacity after 30st cycles. Moreover, for SIB cycling was performed typically between 4.5 and 2.0V vs. Na|Na+ at a constant current of 12.0 mAg-1, equivalent to 0.1 C-rate. In this case, the stoichiometry 0,5Li0Na1.0Mn0.4Ni0.5Ti0.1O2-0,5LiMn1.4Ni0.5Ti0.1O4 showed an initial specific capacity, ca. 118 mAh g-1. Thus, by possessing interesting properties electrochemical we believe that these materials could be a potential electrode for the development of high-power rechargeable Li-ion batteries and Na-ion batteries.